Interactive landscaping: a business development hub for hybrid professionals - Ndlovu, Nomusa (My University, 2011)
Designing a building from the inside out is done by “Discovering the kinds of places people need for themselves for their emotional selves to grow and develop and feel safe, for relationships to function effectively.” (Franck, Lepori 2007:98) It is about an internal process of architectural design rather than an external one. Peter Zumthor achieves this in the Thermal Bath Vals when he used ‘the ritual of Bathing’ as a stimulus for design. He took account of the “body’s needs in space, sounds, temperature, that were required at different moments of the design. His explorations were independent of rigid form but right from the beginning there was a feeling of a silent world inside the mountain. In a similar way the design of the Business Development Hub in Zimbabwe resulted from the study and mapping of the ‘rituals’ of the professional’s routes within the facility. The process together with the conducted research was about discovering how architecture can provide environments that aid in professional improvement and through facilities and exposure reintegrate the Hybrid professional back into the economy by playing a large role in supporting professionals in their business venture. My research has lead me to the conclusion that because of the nature in which hybrid professionals conduct their business ventures, what is needed is an architecture that intensifies interaction between professionals and provides them with a platform upon which formal, informal and spontaneous exchange can take place between professionals. The challenge is to design the buildings’ internal fabric to continually act as a stimulator for heightened chance encounters and interaction.